A standards-based network monitoring system - Díaz, Francisco Javier
This article describes a system meant to provide monitoring services using Simple Network Management Protocol (SNMP) and the Java 2 Platform, Standard Edition (J2SE). The architecture of the system is based on JMX (Java Management eXtensions), and is composed of agents and managers. Each Java agent is a mediator between a set of SNMP agents of a network and the management applications. When the number of administered SNMP agents is large, assigning a Java agent to handle each one of them would be not only complex, but unfeasible if the device subject to monitoring does not support Java or if the device is unreachable for security matters. To avoid this problem without interfering with the security policies of a network, we propose an architecture in which a Java agent or master concentrates and sends the management application all the monitoring information of the SNMP sub-agents. This proposal simplifies the process of administration of the devices, increases the internal security of the monitored network, allows monitoring of not java-enabled devices and diminish the network traffic considerably. Additionally, the system provides a manager with a simple but high quality user interface to facilitate the remote administration of the Java agents.